Party Control, Intraparty Competition, and the Substantive Focus of Women's Parliamentary Questions: Evidence from Belgium. Issue 1 (22nd March 2023) - de Vet, Benjamin; Devroe, Robin
Abstract: Parliaments are still often criticized for being gendered—that is, for maintaining problematic inequalities between male and female officeholders. While research highlights how female members of parliament (MPs) take the floor less often than men, especially during debates on "hard" policy domains, much remains unknown about the role that political parties play in fostering such differences. Drawing on a novel data set on the use of parliamentary questions in Belgium ( N = 180, 783), this article examines gendered patterns in the substantive focus of MPs' parliamentary work. It confirms that differences in the issue concentrations of male and female MPs exist, but they are larger when access to the floor is more restricted and party control is stronger. Our findings yield important insights into the gendered side effects of parliamentary procedure and shed some light on the "choice versus coercion" controversy with regard to women's substantive focus of parliamentary work.